Marek Waleriusz i kruk. Historia pewnej symbiozy bitewnej (Liv. 7.26) - Matusiak, Patrycja (Collectanea Philologica, 2025)
In the seventh book of Ab Urbe Condita, Titus Livius describes an extraordinary phenomenon of battle symbiosis involving a bird. During the campaign against the Gauls in 349 BC, a Gallic warrior challenged a Roman to single combat – this Roman was Marcus Valerius. During the fight, a raven landed on his helmet and aided him in the duel, which earned him the cognomen Corvinus. Livy presents this event within the framework of monomachy, aristeia, and the etymological explanation of the epithet, emphasizing the role of the gods. However, this story may also be a reinterpretation of avian imagery appearing on Gallic warriors’ helmets, such as the so-called Ciumeşti Helmet, discovered by archaeologists in 1961 in western Romania.